Characterization of echolocation calls from insectivorous bats in Puting Bato Cave 5, Burdeos, Polillo island, Philippines - Taray, Kirk J.; Alviola, Phillip A.; Cruz, Florante A.; Lit, Ireneo L. Jr.; Gonzalez, Juan Carlos T. (2021)
"Acoustic recording is rarely applied in studying Philippine bats, which is reflected by the scarcity of related publications in the country. As a result, the echolocation calls of many local bat species are still unknown, and a reliable bat call library does not exist. Here, we described the echolocation call of some insectivorous bats in Polillo Island and used the call characteristics to define each species." - Abstract.
Includes bibliographical references.
Keywords: Bat sounds -- Philippines -- Polillo Island; Bats -- Philippines -- Polillo Island; Bioacoustics -- Philippines -- Polillo Island